2017
DOI: 10.18203/2349-3933.ijam20173246
|View full text |Cite
|
Sign up to set email alerts
|

A study of treatment outcomes of pulmonary tuberculosis and extrapulmonary tuberculosis patients in a tertiary care centre

Abstract: Background: Directly observed treatment remains one of the most widely-accepted global health interventions for tuberculosis. Tuberculosis treatment outcome is one of the performance indicators of the programme set by World Health Organization.Methods: This study was conducted in a tertiary care centre Chennai. A retrospective analysis of the profile and treatment outcome of all tuberculosis patients registered from January 2015 to December 2015 at DOTS centre under RNTCP was conducted. Data on treatment outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
0
3
Order By: Relevance
“…We found that the overall TB treatment success (i.e. having an outcome of cured or treatment completed) at the end of the treatment was 86.2%, which is similar to other resource-constrained countries such as India (81-83%) [23][24][25], Ethiopia (85.6%) [26], Nigeria (83.1%) [27], Uzbekistan (83%) [28], Thailand (78.5-87.5%) [29], and higher than war affected countries such as Somalia (81.8%) [30], Iran (83.1%) [31] and Afghanistan (77.7%) [32]. However, the treatment success rate in our study was lower than the treatment success rate reported in the previous studies in Pakistan [13,33].…”
Section: Discussionsupporting
confidence: 67%
“…We found that the overall TB treatment success (i.e. having an outcome of cured or treatment completed) at the end of the treatment was 86.2%, which is similar to other resource-constrained countries such as India (81-83%) [23][24][25], Ethiopia (85.6%) [26], Nigeria (83.1%) [27], Uzbekistan (83%) [28], Thailand (78.5-87.5%) [29], and higher than war affected countries such as Somalia (81.8%) [30], Iran (83.1%) [31] and Afghanistan (77.7%) [32]. However, the treatment success rate in our study was lower than the treatment success rate reported in the previous studies in Pakistan [13,33].…”
Section: Discussionsupporting
confidence: 67%
“…In this study, the overall TB treatment success rate is higher from previous published studies in different countries; studies from India reported the overall treatment success rates were (81%) [23], (83%) [24], (84.21%) [25], and (86%) [26], in Thailand the success rate was (78.5%) for patients in the TB Case Management cohort, while the success rate is high (87.5%) for patients in the National Health Security Office cohort [27], Iran (83.1%) [28], Uzbekistan (83%) [29], Denmark (80.5%) [30], Malaysia (67.26%) [31], Ethiopia (85.6%) [32], Somalia (81.8%) [33], Nigeria (83.1%) [34], in…”
Section: Discussioncontrasting
confidence: 61%
“…In this study, the overall TB treatment success rate is higher from previous published studies in different countries; studies from India reported the overall treatment success rates were (81%) [17], (83%) [18], (84.21%) [19], and (86%) [20], in Thailand the success rate was (78.5%) for patients in the TB Case Management cohort, while the success rate is high (87.5%) for patients in the National Health Security Office cohort [21], Iran (83.1%) [22], Uzbekistan (83%) [23], Denmark (80.5%) [24], Malaysia (67.26%) [25], Ethiopia (85.6%) [26], Somalia (81.8%) [27], Nigeria (83.1%) [28], in…”
Section: Discussioncontrasting
confidence: 61%